The design of a rubric to evaluate laboratory reports in astronomy: academic literacy in the disciplines (2014)
A rubric was developed to evaluate laboratory reports written by undergraduate students of astronomy and astrophysics from Universidad Católica de Chile. The process of elaboration, peer validation, and application of the rubric to the evaluation of written tasks extended from August 2011 to August 2012. The instrument proved to be effective as an assessment tool that guides teachers towards the fundamental criteria that must be considered when evaluating their students’ writing. Moreover, the instrument provides useful guidelines to direct students’ attention towards the critical components of the laboratory report genre.Se elaboró una rúbrica para evaluar informes de laboratorio escritos por estudiantes de pregrado de la carrera de Astronomía y Astrofísica de la Universidad Católica de Chile. El proceso de elaboración, aplicación y posterior validación de la rúbrica por expertos abarcó desde agosto del 2011 hasta el mismo mes del 2012. El instrumento mostró efectividad como una herramienta que guía a los profesores hacia los criterios fundamentales que deben considerarse cuando se evalúan informes de laboratorio. Además, la rúbrica propuesta establece parámetros que enfocan la atención del estudiante hacia las características fundamentales del género informe de laboratorio.